Trading options for edge a professional guide to volatility trading - Sebastian, Mark 1978-; Taylor, L. Celeste (De Gruyter, 2022)
If you have experience in option trading, or a strong understanding of the options markets, but want to better understand how to trade given certain market conditions, this is the book for you. Mark Sebastian's new edition will teach trade evaluation, using Greeks, trading various spreads under different market conditions, portfolio-building, and risk management. Sebastian's approach will help traders understand how to find edge, what kind of trade under what conditions will capture edge, and how to create and successfully hedge. The book demonstrates how to structure a portfolio of trades that makes more money with less risk.